Uterine Prolapse, Mobile Camp Approach and Body Politics in Nepal - Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2011)
Various studies show that more than 600,000 women in Nepal are suffering from prolapsed uterus and that 200,000 of those needed immediate surgery. Many of the women with prolapse could recall the exact moment they first felt the prolapse and found difficulty to share the problems due to fear of stigma. Stories ranged from seven days immediately after the first delivery to after the birth of the fifth or sixth child; during cooking rice to sneezing and long coughing; fetching water in a big bucket to working in the field. If detected at an early stage, uterine prolapse (UP) can be controlled by pelvic exercises. For severe cases, the remedy is to insert a ring pessary to stop it from descending which has to be changed every four months. In extreme cases, uterine tissue protrudes from the vagina causing extreme discomfort. The only remedy is hysterectomy in which the uterus is surgically removed. The operation costs are about NRs 20,000. The Government of Nepal and other donor organizations have allocated funds to provide services to about 10,000 to 12,000 women suffering from uterine prolapse as humanitarian support each year and services are likely to be expanded in future. Women suffering from UP have not been able to get benefit from such assistance due to deep rooted socio-cultural perceptions and practices. The number of suffering women, on the other hand, would not decrease from existing curative management policy without hammering the root causes of UP. Moreover, a clear vision and strategy is needed to shift from humanitarian aid to a more sustainable public health intervention. Keywords: Camp Approach; Humanitarian Aid; Socio-cultural Practices; Sustainable Policy; Uterine Prolapse DOI: 10.3126/dsaj.v4i0.4511 Dhaulagiri Journal of Sociology and Anthropology Vol.4 2010 pp.21-40